Getting CHO host cell protein analysis up to speed. (February 2015) - Leiss, Michael; Meier, Monika; Pester, Oxana; Aschner, Marion; Wedekind, Frank; Wiedmann, Michael; Wegele, Harald
Aim: Host cell proteins represent a major process-related impurity in recombinant biotherapeutics. Present work reports about a fully automated platform based on a cobas instrument (Roche Diagnostic GmbH, Mannheim, Germany) allowing high-throughput determination of host cell proteins.Materials & methods : The instrument combines automated sample preparation with electrochemiluminescence-based detection technology, facilitating highly sensitive and accurate detection.Results: Our data shows that the assay performs readily comparable to conventional ELISAs, but outperforms in speed, sample throughput and by its superior linear range. Comparison of ELISA and electrochemiluminescence immunoassay validation results from more than ten independent validations of clinical product testing methods supports our comparability claim.Conclusion: The electrochemiluminescence immunoassay represents a milestone for bioprocess impurity testing and abolishes the sample throughput limitations posed by conventional ELISA.